1995
DOI: 10.1080/00140139508925176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moisture absorption in clothing on the human heat balance

Abstract: A theory of moisture absorption in clothing, with the associated effects of heat transfer, was developed and applied in a computer model. The model considers the body, underclothing, an outer layer, and the adjacent air layer. The theory was checked with an experiment involving four subjects. They wore heavy woollen clothing, which was either initially dry or humid, in both a warm and a cool environment. Model calculations and experimental results agree approximately upon the timing and magnitude of the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…With the same or a lesser thickness, the textile samples impermeable to hot water steam limited heat transfer due to exposure to steam more efficiently than the permeable samples. At the beginning of the exposure to the steam jet, the permeable samples showed a peak of heat flux probably due to the complex phenomena of condensation, diffusion and absorption of water inside the sample, which results in the release of high levels of heat (Farnworth 1986;Lotens and Havenith 1994). Waterproofing of the permeable samples led to the loss of these phenomena, which also explain the results observed with TX, an impermeable sample.…”
Section: Discussionmentioning
confidence: 81%
“…With the same or a lesser thickness, the textile samples impermeable to hot water steam limited heat transfer due to exposure to steam more efficiently than the permeable samples. At the beginning of the exposure to the steam jet, the permeable samples showed a peak of heat flux probably due to the complex phenomena of condensation, diffusion and absorption of water inside the sample, which results in the release of high levels of heat (Farnworth 1986;Lotens and Havenith 1994). Waterproofing of the permeable samples led to the loss of these phenomena, which also explain the results observed with TX, an impermeable sample.…”
Section: Discussionmentioning
confidence: 81%
“…However, this is not logistically feasible when breaks between halves or events are short, as clothing removal and re-dressing takes valuable cooling time, or is problematic when large groups of athletes are to be cooled. With this in mind, various strategies have been implemented in an attempt to maintain performance in the heat and regulate body temperature, these include: appropriate pacing (Tucker et al 2004); clothing design (Lotens and Havenith 1994); acclimatisation/acclimation to heat (Sunderland et al 2008); hydration strategies (Galloway and Maughan 2000); pre-cooling (Duffield and Marino 2007) and artificial (external) cooling (Mitchell et al 2001). Techniques for achieving artificial cooling typically utilise smaller body surface areas than that covered during CWI and include: ice vests or phase change garments (PCG; Duffield et al 2003), jackets or caps (conductive cooling) (Armstrong et al 1995); air cooled garments (ACG) or fans (convective/evaporative cooling; Chinevere et al 2008), hand immersion (HI) (conductive cooling; House et al 2003) and liquid cooled garments (LCG, conductive cooling; Vernieuw et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Also, heart rate was significantly lower during the experimental period with DC clothing (Figure 4) and the loss of In general, garments worn for sports or work should allow rapid transmission of metabolic heat and sweat from the body to the surroundings, so reducing internal heat stress and allowing exercise to be performed effectively (Hayashi & Tokura, 1999, 2000Park et al, 2006). The properties of clothing materials relevant to heat and moisture transfer are thermal insulation, moisture absorption and water vapour permeability (Lotens, 1993;Lotens & Havenith, 1995;Park et al, 2005). In the present study, the fabric dyed with persimmon extract showed higher moisture regain, water vapour transmission and air permeability, and slightly lower thermal resistance than did undyed fabric, a result similar to that found previously (Park, 1995;Yi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%